PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) BERBASIS SOAL OPEN – ENDED UNTUK MENINGKATKAN KOMUNIKASI MATEMATIKA - Fauzi Wildad; Budi Waluya; M Masrukan (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2019)
This research aims to determine the feasibility and effectiveness of the application of learning using social arithmetic teaching books with Realistic Mathematics Education (RME) approach based on Open-Ended problem. The research design used in this research is Research and Development (R and D) with Plomp model. Subjects in this study were students of Class VIII SMP Islam Terpadu Askhabul Kahfi 2017 / 2018. implementation design using Posttest Only Control-Group Design. The analysis used in the form of analysis of expert validation results and effectiveness test. Post test results on the class performed by the action are compared to the non-action class and to ensure it is done by (1) Complete Test, (2) Different Test, and (3) Simple Linear Regression Test. Based on the results of research and discussion, obtained the conclusion that (1) Arithmetic learning devices with RME approach developed valid is used based on the expert expert judgment. And according to the results of small and large class test, and (2) Arithmetic learning tools with RME approach developed effectively. This is indicated by (a) the average value of evaluation of classroom communication skills using 73, 42 (μ 70) and 76,6% (π 75%) classical completeness; (b) the average rate of classes using the application of mathematics learning tools with RME approach based on open-ended problem (73,42) is greater than the class that does not use the application of mathematics learning tool with RME approach based on open-ended problem (64,57) and (c) from the regression test obtained tcount = 2.012, tcount (2.012) ttable (1.99834).